Networks, Communities and Markets in Sub-Saharan Africa: Implications for Firm Growth and Investment. - Fafchamps, M (OUP, 2001)
This paper examines how relationships and networks affect market exchange in Sub-Saharan Africa. After noting that market exchange arguably plays a larger role in Africa than in developed economies, we show that the presence of transactions costs naturally leads market participants to enter in long-term trading relationships. These relationships form business networks that shape market outcomes. We argue that network segmentation can have large efficiency and equity costs, particularly in international trade. Because of network externalities, groups and countries that are familiar with a particular activity tend to continue investing in that activity. The presence of networks and non-convex transactions costs also complicates the analysis of market competition. Implications for future research are briefly discussed.